GPS TEC response to Pc4 "giant pulsations". Issue 2 (23rd February 2016) - Watson, Chris; Jayachandran, P. T.; Singer, Howard J.; Redmon, Robert J.; Danskin, Donald
Abstract: Variations in ionospheric total electron content (TEC) associated with ultralow frequency (ULF) magnetic field variations in the Pc4 (6.7–22.0 mHz) frequency band were observed in the early morning sector. TEC variations were observed by the Global Positioning System (GPS) receiver in Sanikiluaq, Nunavut (56.54°N, 280.77°E), which is located near the equatorward edge of the auroral region. Small‐amplitude Pc4 ULF waves were observed by the Sanikiluaq ground magnetometer and by the geosynchronous GOES 13 satellite. TEC and magnetic field both exhibited narrowband, highly regular, quasi‐sinusoidal waveforms, with high correlation and coherence indicating a clear link between TEC variations and Pc4 ULF activity. Variations in TEC and 30–50 keV electron flux observed by GOES 13 were also highly correlated and coherent. TEC variations observed directly above Sanikiluaq were in antiphase with eastward magnetic field variations on the ground, while TEC variations observed at the footprint of the GOES 13 satellite were in phase with GOES radial magnetic field and 30–50 keV electron flux. Intermittent occurrence of TEC variations observed by multiple GPS satellites indicated a localized ionospheric response to the Pc4 activity. This is the first clear evidence of a TEC response to these so called "giant pulsations (Pgs)." By applying a multisatellite triangulation technique, the phase velocity, group velocity, and azimuthal wave number of TEC variations were also calculated for an interval of highly coherent measurements. The phase and group propagation velocities were 2–7 km/s and 1–3 km/s north and westward, respectively, while the azimuthal wave number ranged from −35 to −310. Key Points: TEC responds to Pc4 "giant pulsations (Pgs)" TEC and magnetic field exhibit similar quasi‐sinusoidal, highly regular waveforms Multisatellite observations indicate that the TEC response was intermittent and localized